Uji Aktivitas Antibakteri Obat Kumur Ekstrak Daun Belimbing Wuluh (Averrhoa Bilimbi L.) Terhadap Bakteri Streptococcus mutans Penyebab Karies Gigi - Muhammad Nurul Fadel; Endang Setyowati; Yulis Trinovitawati; Wahid Sabaan (CERATA Jurnal Ilmu Farmasi, 2021)
Dental caries is a disease of the oral cavity caused by Streptococcus mutans bacteria. The mouthwash used continuously will cause side effects. So it is necessary to develop mouthwash preparations from natural ingredients, one of the plants is wuluh starfruit leaves (Averrhoa bilimbi L.) which contain flavonoids, tannins and saponins as antibacterial agents. The aim of this study was to determine the activity of the formulas for the mouthwash of wuluh starfruit leaves extract (Averrhoa bilimbi L.) which can affect the bacteria Streptococcus mutans. Research using the disc diffusion method, mouthwash made in 3 formulas, namely FI, FII, FIII with concentrations of 10%, 15% and 20%, which were placed on TSA media that had been overgrown with Streptococcus mutans bacteria incubated and the diameter of the inhibition zone (zone). clear). The results of the research on formula I (10%) on the first day get an average of 4.3 mm and day 14 get an average of 4 mm, this includes the classification of weak inhibition zones (less than 5 mm), formula II (15% ) get an average of 6.3 mm and day 14 get an average of 6 mm including the classification of moderate inhibition zone (5mm-10mm), formula III (20%) gets an average of 9.5mm and day 14 gets an average an average of 9.2 mm including the moderate inhibition zone classification (5mm-10mm), while the positive control (Povidone Iodine 1%) got an average of 13.8 mm and the 14th day got an average of 13.5 mm including the strong inhibition zone classification (more than 10mm) and negative control haven't drag zone. Based on the results of the data above, the formula of wuluh starfruit leaves mouthwash (Averrhoa bilimbi L.) can inhibit Streptococcus mutans bacteria.